Preliminary study of biliary microbiota and identification of bacterial species associated with pigmented gallstone formation - Zhang, Riyuan; Chen, Chong; Zheng, Suhua; Zhang, Jianwei; Chen, Weiling; Chen, Zhimin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPigmented gallstone disease (PGS) is prevalent in China. Biliary microbiota is certified to be related to the PGS formation.MethodsWe performed 16S sequencing on both bile and gallstone samples in 16 patients with gallstone disease. We analyzed the microbial composition of the biliary tract and identified crucial bacteria related to the formation of PGS.ResultsBiliary tract bacterial composition analysis showed heterogeneity of dominated genus among individuals and correlation in bacterial composition between bile and gallstones. We screened 10 prevalent genera with significant abundance in the bile and gallstones. Actinomyces, Streptococcus, and Achromobacter had a significantly higher abundance in gallstones than in bile (P < 0.05). Furthermore, we identified 32 species that harbored uidA, pldA, and plc genes that encoded β-glucuronidase or phospholipase. Finally, we observed an enriched membrane transport for bile resistance through biliary microbiota.Conclusionβ-glucuronidase-producing Streptococcus spp., including Streptococcus dysgalactiae and Streptococcus agalactiae, and Parabacteroides merdae, harbored both uidA and pldA genes and were found to be crucial bacterial species in PGS formation.